Development of a market-driven training model for rural women in Iran by using a qualitative paradigm - Allahmoradi, Zeynab; Hosseini, Seyed Jamal Farajallah; Lashgarara, Farhad; Moghaddasi, Reza (Frontiers in Sociology, 2024)
Training programs aimed at empowering rural women in Kurdistan, Iran, have fallen short of their goals. This study offers a unique understanding of how contextual factors and cultural nuances impact the effectiveness of market-driven training programs for rural women in Kurdistan. Objectives: This study explored factors affecting the effectiveness of market-driven training programs for rural women in Kurdistan. Methods: A qualitative approach using grounded theory methodology was employed. Interviews were conducted with 23 key informants, including rural women and experts. Data analysis with MAXQDA software identified seven categories and a core category related to market-driven training. Findings: The study revealed that successful implementation of market-driven training hinges on various external and internal factors. These include access to markets, facilities, and funding, along with effective monitoring of business activities. Additionally, rural community culture and the purchasing power of women were identified as key intervening conditions impacting program success. When implemented effectively, market-driven training programs have the potential to empower women, reduce rural migration, and improve product quality. Recommendations: The research suggests that future training programs should adopt a multi-dimensional approach that addresses the identified factors to achieve sustainable positive outcomes for rural women in Kurdistan.